(untitled) (Bangladesh Journal of Medical Science, 2026)
Dental materials are commonly used in dentistry to treat dental issues and restore the normal function and appearance of teeth. Although these materials are beneficial, they can sometimes cause adverse effects in the mouth. These effects may involve both the hard tissues, like teeth, and the soft tissues, such as the gums and tongue. Common reactions include geographic tongue, recurrent aphthous ulcers, contact stomatitis, and amalgam tattoos. In some cases, dental materials can also lead to tooth discoloration, especially when the restoration fails or leaks. If the restorative material does not properly seal the tooth, it may affect the dental pulp, leading to inflammation or even pulp necrosis. Furthermore, understanding how dental materials such as metals, ceramics, and composites are classified is important because it helps determine how they interact with oral tissues and the potential problems they may cause. Another key factor is biocompatibility, which ensures that dental materials do not harm the tissues in the mouth. This highlights the need to select safe materials to prevent unwanted reactions. This review explores the relationship between dental materials and common oral health issues, and emphasizes the importance of using biocompatible materials to reduce side effects and improve patient outcomes. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 702-717